2017
DOI: 10.5430/cns.v6n2p47
|View full text |Cite
|
Sign up to set email alerts
|

Fever or not fever – that’s the question: A cohort study of simultaneously measured rectal and ear temperatures in febrile patients with suspected infection

Abstract: Objective: To study how ear and rectal body temperatures relate to each other over time in febrile patients. Methods: Descriptive cohort study with repeated measurements. The setting was a Unit for Infectious Diseases at a county hospital in Sweden. Patients, ≥ 18 years, admitted for suspected infection and with a rectal or ear temperature of ≥ 37.5• C were invited. 16 females and 24 men, 19 to 94 years were included. Ear and rectal temperature was measured simultaneously every two hours for one day.Results: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Elevated temperature, assessed as fever, is an important sign often decisive for further action in case of suspected infectious disease [20][21][22] , and a legitimate reason for accessing the resources the healthcare system offers when the patient seeks care 23 . Since normal body temperature varies between individuals due to, among other things, sex, age, inflammatory processes and comorbidities, it is reasonable to assume that the temperature assessed as fever also varies between individuals [24][25][26] . Instead of starting from a predetermined limit value, a temperature rise at least 1°C increase from the individual's normal body temperature and a simultaneous malaise can be defined as fever 12,20 .…”
Section: Assessment Of Changes In Body Temperature and Oxygen Saturationmentioning
confidence: 99%
“…Elevated temperature, assessed as fever, is an important sign often decisive for further action in case of suspected infectious disease [20][21][22] , and a legitimate reason for accessing the resources the healthcare system offers when the patient seeks care 23 . Since normal body temperature varies between individuals due to, among other things, sex, age, inflammatory processes and comorbidities, it is reasonable to assume that the temperature assessed as fever also varies between individuals [24][25][26] . Instead of starting from a predetermined limit value, a temperature rise at least 1°C increase from the individual's normal body temperature and a simultaneous malaise can be defined as fever 12,20 .…”
Section: Assessment Of Changes In Body Temperature and Oxygen Saturationmentioning
confidence: 99%
“…This has been confirmed by Mackowiak and Worden [15], who showed that the thermometer used by Wunderlich measured 1.4°C to 2.2°C higher than modern digital devices. However, as the normal body temperature shows individual variation, a more logical approach is that the same should hold true for the febrile range [16][17][18]. We tested this hypothesis in a large multicenter study by measuring ear temperatures in 2006 apparently healthy individuals aged [2,4], and 10 to 89 years, of whom 1,700 also claimed that their temperature was assessed as fever by themselves and their children.…”
Section: Body Temperature and The Concept Of Difftempmentioning
confidence: 99%